Concurrent high-intensity interval training and probiotic supplementation improve associative memory via increase in insulin sensitivity in ovariectomized rats - Zeinab Bayat; Arsalan Damirchi; Meysam Hasannejad-Bibalan; Parvin Babaei (BMC, 2023)
Abstract Objectives Metabolic syndrome (MetS) is a serious concern among postmenopausal women which predisposes them to cardiovascular and cognitive disorders. Healthful diet and exercise training have been essential strategies to prevent the progress of MetS. The aim of this study was to evaluate the effect of supplementation with a native potential probiotic and high-intensity interval training (HIIT) for 8 weeks on retention of associative memory in rats with ovariectomy- induced metabolic syndrome. Method Thirty-two female ovariectomized Wistar rats were divided into four groups (n = 8/group): Control (OVX + Veh), exercise (OVX + Exe), probiotic (OVX + Pro), exercise with probiotic (OVX + Exe + Pro). One sham surgery group was included as a control group. Animals received 8 weeks interventions, and then were tested in a step through passive avoidance learning and memory paradigm, to assess long term memory. Then serum levels of adiponectin, insulin and glucose were measured by ELISA and colorimetry respectively. Data were analyzed by Kruskal-Wallis, Mann-Whitney and also One-way analysis of variance (ANOVA). Results Eight weeks of HIIT and probiotic supplementation caused an increase in step through latency and shortening of total time spent in the dark compartment in OVX + Exe + Pro group compared with OVX + Veh group. Also significant increase in serum adiponectin levels, in parallel with a reduction in glucose, insulin and HOMA-IR were achieved by the group of OVX + Exe + Pro. Conclusion The present study indicates that HIIT combined with probiotics supplementation for 8 weeks effectively improves associative memory in MetS model of rats partly via improving insulin sensitivity and adiponectin level.